Effect of antenatal multiple micronutrient supplementation on anthropometry and blood pressure in mid-childhood in Nepal: follow-up of a double-blind randomised controlled trial - Dr. Delan Devakumar, PhD; Shiva Shankar Chaube, BEd; Prof. Jonathan C K Wells, PhD; Naomi M Saville, PhD; Prof. Jon G Ayres, MD; Prof. Dharma S Manandhar, FRCP; Prof. Anthony Costello, FMedSci; Prof. David Osrin, PhD (Elsevier, 2014)
Background: In 2002-04, we did a randomised controlled trial in southern Nepal, and reported that children born to mothers taking multiple micronutrient supplements during pregnancy had a mean birthweight 77 g greater than children born to mothers taking iron and folic acid supplements. Children born to mothers in the study group were a mean 204 g heavier at 2·5 years of age and their systolic blood pressure was a mean 2·5 mm Hg lower than children born to mothers in the control group. We aimed to follow up the same children to mid-childhood (age 8·5 years) to investigate whether these differences would be sustained. Methods: For this follow-up study, we identified children from the original trial and measured anthropometry, body composition with bioelectrical impedance (with population-specific isotope calibration), blood pressure, and renal dimensions by ultrasound. We documented socioeconomic status, household food security, and air pollution. Main outcomes of the follow-up at 8 years were Z scores for weight-for-age, height-for-age, and body-mass index (BMI)-for-age according to WHO Child Growth Standards for children aged 5-19 years, and blood pressure. This study is registered with the International Standard Randomised Controlled Trial register, number ISRCTN88625934. Findings: Between Sept 21, 2011, and Dec 7, 2012, we assessed 841 children (422 in the control group and 419 in the intervention group). Unadjusted differences (intervention minus control) in Z scores were 0·05 for weight-for-age (95% CI −0·09 to 0·19), 0·02 in height-for-age (−0·10 to 0·15), and 0·04 in BMI-for-age (−0·09 to 0·18). We recorded no difference in blood pressure. Adjusted differences were similar for all outcomes. Interpretation: We recorded no differences in phenotype between children born to mothers who received antenatal multiple micronutrient or iron and folate supplements at age 8·5 years. Our findings did not extend to physiological differences or potential longer-term effects. Funding: The Wellcome Trust.